Digital Sustainability: Pioneering a Greener Future through Innovation and Entrepreneurship - Uday Kumar, N.; Gundarapu, Srinivas (International Journal of Advances in Business and Management Research (IJABMR), 2025)
In an era defined by rapid digital transformation and environmental urgency, digital sustainability emerges as a pivotal strategy for achieving a greener, more resilient future. This paper explores how innovation and entrepreneurship serve as critical drivers in promoting digital sustainability, enabling businesses, governments, and societies to reduce ecological footprints while maintaining economic growth. By integrating cutting-edge technologies such as AI, blockchain, and the Internet of Things (IoT) with sustainable development goals (SDGs), forward-thinking entrepreneurs are reshaping industries from energy and agriculture to logistics and manufacturing. The study presents a multi-dimensional framework that examines the intersection of digital innovation and sustainability practices, highlighting successful case studies from global start-ups and enterprises. It investigates how digital tools are optimising resource use, lowering carbon emissions, and fostering circular economies. Furthermore, the paper enquires about the role of digital entrepreneurship in addressing systemic environmental challenges and creating scalable solutions aligned with ESG (Environmental, Social, and Governance) principles. Through a combination of theoretical analysis and empirical evidence, the paper points out the revolutionary value of digital entrepreneurship in driving sustainable innovation. It also addresses key barriers such as digital inequality, ethical considerations, and the need for supportive policy ecosystems. The results provide a deeper understanding of how digital sustainability mitigates environmental risks and opens new pathways for inclusive, green economic development.